Intergration of Smart Healthcare Information Systems / Premjit Singh Dulku - Premjit , Singh Dulku (2002)
This project presents a Smart Healthcare Information System (SHIS), which hospitals and medical centers can use to improve their services. SHIS provides a set of integrated services and is web based. The system comprises of several modules, which include patient, insurance and billing, pharmaceutical, healthcare provider, and medical center information systems. It also provides a data analysis system for analyzing medical data. With this system, hospital staff (e.g, administrators, nurses) can perform their tasks (e.g, retrieving patient information, recording diagnostic and treatment details) more quickly and efficiently. Patients can also use the system to view their records and make online appointment. The general public can access the system to obtain general information such as expertise available and information about upcoming events. The system incorporates security features, which allows only authorized users to access confidential information. The project documentation contained herein encompasses the literature review and system analysis of the Integration of Smart Health Care Information System, or in short, IntSHIS. Lots of details has been put towards the software and hardware involved which includes reasoning as to why particular configurations are favored over others, which are also mentioned. It contains technical details as well as some conclusions that have been reached after the study of the specified tools. Without doubt, most of the information gleaned for this section was taken off various Internet articles as well as some books related to the project that was developed. All this explanation, be it on integration or interaction across different components, covers the 5 modules which are discussed and will be introduced under the introduction. The methodology discussed is primarily on basic yet important software engineering principles. This would be applied throughout the development phases of the system, which includes system analysis, design, testing and so on. The method that is selected to develop and test the system too mentioned here. The system design as well as the process taken to develop the system is covered in the sections and short captions which would illustrate the final working system that has been developed. Extensive research and background surveys have been done on all topics involved have been made prior to the commencement of actual coding and documentation. This has been done to ensure a higher level of accuracy in the designing process together with the elimination of redundancy occurrence. Furthermore, a better knowledge base to begin with was acquired. It is hoped that the reader of this thesis report obtains an informative yet enriching document regarding the system that has been integrated.